Species‐level drivers of avian centrality within seed‐dispersal networks across different levels of organisation - Moulatlet, Gabriel M.; Dáttilo, Wesley; Villalobos, Fabricio (The Journal of animal ecology, 2023)
Bird–plant seed‐dispersal networks are structural components of ecosystems. The role of bird species in seed‐dispersal networks (from less [peripheral] to more connected [central]), determines the interaction patterns and their ecosystem services. These roles may be driven by morphological and functional traits as well as evolutionary, geographical and environmental properties acting at different spatial extents. It is still unknown if such drivers are equally important in determining species centrality at different network levels, from individual local networks to the global meta‐network representing interactions across all local networks. Using 308 networks covering five continents and 11 biogeographical regions, we show that at the global meta‐network level species' range size was the most important driver of species centrality, with more central species having larger range sizes, which would facilitate the interaction with a higher number of plants and thus the maintenance of seed‐dispersal interactions. At the local network level, body mass was the only driver with a significant effect, implying that local factors related to resource availability are more important at this level of network organisation than those related to broad spatial factors such as range sizes. This could also be related to the mismatch between species‐level traits, which do not consider intraspecific variation, and the local networks that can depend on such variation. Taken together, our results show that the drivers determining species centrality are relative to the levels of network organisation, suggesting that prediction of species functional roles in seed‐dispersal interactions requires combined local and global approaches. Las redes de dispersión de semillas entre aves y plantas son componentes estructurales de los ecosistemas. El rol de las especies de aves en estas redes de dispersión de semillas (de menos [periféricas] a más conectadas [centrales]), determina los patrones de interacción y sus servicios ecosistémicos. Estos roles pueden ser impulsados por rasgos morfológicos y funcionales, propiedades evolutivas, geográficas y ambientales que actúan en diferentes extensiones espaciales. Todavía se desconoce si dichos impulsores son igualmente importantes para determinar la centralidad de las especies en diferentes niveles de red, desde redes locales individuales hasta la meta‐red global que representa todas las interacciones en las redes locales. Usando 308 redes abarcando cinco continentes y once regiones biogeográficas, mostramos que a nivel de meta‐red global, el tamaño de la distribución geográfica de las especies fue el factor más determinante de la centralidad de las especies, con especies más centrales siendo aquellas que tienen distribuciones más grandes, lo que les facilitaría la interacción con un mayor número de plantas y por lo tanto el mantenimiento de las interacciones de dispersión de semillas. A nivel de las redes locales, la masa corporal fue el único impulsor con un efecto significativo, lo que implica que los factores locales relacionados con la disponibilidad de recursos son más importantes en este nivel de organización que los relacionados con factores espaciales amplios, como el tamaño de las distribuciones. Esto también podría estar relacionado con el desajuste entre los rasgos a nivel de especie, que no consideran la variación intraespecífica, y las redes locales que pueden depender de dicha variación. En conjunto, nuestros resultados muestran que los impulsores que determinan la centralidad de las especies en las redes de interacción son relativos a los niveles de organización de la red, lo que sugiere que la predicción de los roles funcionales de las especies en las interacciones de dispersión de semillas requiere enfoques locales y globales combinados.